Navigating The Digital Threat: A Pentahelix Approach To AI-Driven Data Security In Smart Cities - Puspitasari, Chasandra Puspitasari; Pradana, Antonio Heltra (UPT P2M State Polytechnic of Malang, 2025)
Smart cities provide creative approaches to urban growth, but they also face significant security and data management issues. The necessity for cooperative methods to safeguard sensitive data is highlighted by the rising incidence of cyberattacks and data misuse. In order to develop a shared responsibility for data protection in smart cities, this study uses the Pentahelix framework, which involves the government, academics, industry, communities, and media. A framework that guarantees accountability, transparency, and group control over data is developed by synthesizing pertinent literature, criticisms, and concepts using a qualitative descriptive method. Additionally, the use of artificial intelligence (AI) is examined as a challenge as well as an enabler. While AI improves data security by utilizing anomaly detection, predictive analytics, and automated response, it also poses issues related to ethical governance and privacy. The results imply that multi-stakeholder cooperation combined with AI-driven tactics can improve resilience against digital threats, guaranteeing smarter and safer urban ecosystems.